Genital Injuries: Are They Telling us Something about Sexual Violence? - Carolina Orellana-Campos (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2020)
Abstract Genital injury has a forensic relevance after a sexual assault and it has been discussed and investigated among professionals who work in this field. To analyze the studies published in the last decades, the present review examines different factors that may influence this finding, first clarifying terms of the forensic field, such as the peculiarity of the legal medical examination, and the distinction of the terms "legal" and "anatomical" vagina. Finally, it analyses if it is possible that the existence of these injuries in victims explain the lack of consent in sexual contact, and to clarify the meaning of the absence of injuries.